Influence of storage vial material on measurement of organophosphate flame retardant metabolites in urine. (August 2017) - Carignan, Courtney C.; Butt, Craig M.; Stapleton, Heather M.; Meeker, John D.; Minguez-Alarcón, Lidia; Williams, Paige L.; Hauser, Russ
Abstract: Use of organophosphate flame retardants (PFRs) has increased over the past decade with the phase out of polybrominated diphenyl ethers. Urinary metabolites of PFRs are used as biomarkers of exposure in epidemiologic research, which typically uses samples collected and stored in polypropylene plastic cryovials. However, a small study suggested that the storage vial material may influence reported concentrations. Therefore, we aimed to examine the influence of the storage vial material on analytical measurement of PFR urinary metabolites. Using urine samples collected from participants in the Environment and Reproductive Health (EARTH) Study, we analyzed the PFR metabolites in duplicate aliquots that were stored in glass and plastic vials (n = 31 pairs). Bis(1, 3-dichloro-2-propyl) phosphate (BDCIPP), diphenyl phosphate (DPHP) and isopropyl-phenyl phenyl phosphate (ip-PPP) were detected in 98%, 97% and 87% of duplicates. We observed high correlations between glass-plastic duplicates for BDCIPP (rs = 0.95), DPHP (rs = 0.79) and ip-PPP (rs = 0.82) (p < 0.0001). Urinary ip-PPP was an average of 0.04 ng/ml (p = 0.04) higher among samples stored in glass, with a mean relative difference of 14%. While this difference is statistically significant, it is small in magnitude. No differences were observed for BDCIPP or DPHP, however future research should seek to reduce the potential for type II error (false negatives). We conclude that storing urine samples in polypropylene plastic cryovials may result in slightly reduced concentrations of urinary ip-PPP relative to storage in glass vials and future research should seek to increase the sample size, reduce background variability and consider the material of the urine collection cup. Graphical abstract: Highlights: We measured PFR metabolites in duplicate urine samples stored in glass and plastic vials. Concentrations were highly correlated between duplicates. ip-PPP was slightly but significantly higher using glass compared to plastic vials for storage. DPHP and BDCIPP showed no storage difference between the glass and plastic vials.